Green Energy Project`s Efficiency: A Cross-industry Evaluation - Kozhakhmetova, Assel K.; Gabdullin, Kenzhebek T.; Kunanbayeva, Duissekul A.; Tazhiyeva, Samal K.; Kydaybergenova, Renata E. (International Journal of Energy Economics and Policy, 2019)
Renewable energy attracts wide attention of world due to high importance and relevance. The study is devoted to this topic and aims to identify critical Project Management (further PM) knowledge areas those affect efficiency of green energy project, and to reveal PM tools those increase an efficiency. The study investigates 253 high-tech projects from Kazakhstan and compares green energy projects with projects from other industries like Information technologies (further IT), nanotechnologies and communications. Authors use Project Management Planning Quality (further PMPQ) model for measuring the efficiency of these projects and for identifying critical factors of efficiency. Results show that IT projects have highest level of efficiency (cost overrun –12,2%, schedule overrun –2,8%, project performance –8,8), when green energy projects show average level of efficiency (cost overrun – 45,13%, schedule overrun –6,2%, project performance –7,5). Research findings link these results with use intensity of PM processes. Project efficiency evaluation has also revealed critical knowledge areas for green energy projects like project schedule management, communication management, risk and quality management. Thus, authors have suggested tools and techniques from revealed knowledge areas for improving efficiency of project. Keywords: Green Energy Project, Project Efficiency, Project Management, Project Planning, Kazakhstan. JEL Classifications: C39, O21, Q20, Q42 DOI: https://doi.org/10.32479/ijeep.8137